Analisis of Risk Managemen Implementation on Mudharabah and Musyarakah Financing Product at BMT Sidogiri Dampit Branch - Isa kholili (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose and focus of this research is to analyze the pattern of risk management application used by BMT Sidogiri in order to minimize the level of losses that may occur and to find out the risk management pattern used is in accordance with sharia principles so that this becomes the urgency of this research with the hope that in operational practice it can mutual benefit between the BMT and the customer. This research data analysis method uses descriptive techniques/methods with a qualitative approach, namely the researcher describes the phenomenon that is the center of the study and discussion which will eventually produce descriptive data in the form of narratives from respondents combined with theory